Graphene-based materials behaviour for dyes adsorption. (March 2022) - Paton-Carrero, A.; Sanchez, P.; Sánchez-Silva, L.; Romero, A.
Abstract: Due to the environmental damage caused by dye dumping, the scientific community has been researching into different adsorbents in order to mitigate this impact. In this respect, different graphene-based materials with a high adsorption capacity were studied (graphite and graphene oxide and two different types of reduced graphene oxide). In this work, four graphene-based materials with different properties and structures were evaluated. All materials were those obtained at each step in the pathway of oxidation, exfoliation, and reduction of graphite for conversion into reduced graphene. These four materials were characterized in depth by different methods (RAMAN, XRD, EDX, SEM, FTIR). Adsorption variables were researched to demonstrate their great adsorptive rate, which reached in some cases values of over 300 mg/g of adsorbed dye. Therefore, this study established a relationship between the physicochemical properties of the materials and their adsorption capacity. Furthermore, the effect of different variables on the process was studied: temperature, contact time and amount of adsorbent.This study creates new adsorbent materials with a long lifespan, reducing the environmental impact of industry on nature. Graphical Abstract: ga1 Highlights: Combination of surface area and functional groups are the most important variable on dye adsorption. Graphene oxide is the material with the highest value for methylene blue adsorption. Thermal reduced graphene oxide is the material with the highest value for methylene blue adsorption. Temperature plays an important role in the adsorption capacity of the materials.